Caracterización clínico epidemiológica de pacientes con Síndrome Coronario Agudo, Hospital Carlos Andrade Marín. Quito, 2020 - Washington Raúl, Vallejo De la Torre (2021)
ABSTRACT The present degree work "Clinical and epidemiological characterization of patients with Acute Coronary Syndrome, Carlos Andrade Marín Hospital. Quito, 2020" aims to identify risk factors, symptoms and characteristic signs to provide timely care to the population suffering from chest pain and conditions caused by a sudden decrease or blockage of blood supply to the heart, as well as epidemiological aspects because acute coronary syndromes are an important public health problem in our environment, and thus know the preventive measures to be considered based on diagnoses and history of each patient. This is a quantitative study, because statistical records were used to identify patients with acute coronary syndrome in the cardiology service, according to the information provided in the clinical histories; it is descriptive because it allows us to inquire about clinical and epidemiological characteristics; and cross-sectional because it was carried out over a certain period of time. We worked with 222 patients of both sexes, aged between 52 and 85 years, who were hospitalized in the cardiology service and the coronary care unit, with definitive diagnoses of: unstable angina, acute transmural myocardial infarction of the anterior wall, inferior, unspecified site, acute subendocardial myocardial infarction, acute myocardial infarction without other specification. From this group, a sample of 50 patients was taken whose data were taken from the statistics and planning area. Key words: acute coronary syndrome, STEMI, NSTEACS, unstable angina.